Systematic Review of Prevalence and Types of Health Hazards among Seaport Workers in Sub-Saharan Africa - E. W., Muagba Otutozinuchi (African Journal of Clinical Medicine and Pharmacy Research, 2026)
Seaport workers in Sub-Saharan Africa face numerous occupational health risks, yet comprehensive evidence regarding the prevalence and types of these hazards remains limited. This systematic review aimed to collate and synthesize existing research on the occurrence, patterns, and determinants of work-related health hazards among seaport employees, with a particular focus on insights relevant to Eastern and Western regions of Nigeria. A thorough search was performed across Scopus, Web of Science, PubMed, and Google Scholar for publications between 2013 and 2025, using terms such as “seaport workers,” “occupational hazards,” “injuries,” “diseases,” and “environmental exposures.” Studies reporting quantitative or qualitative data on occupational injuries, musculoskeletal disorders, respiratory conditions, hearing impairments, skin ailments, and other work-related health problems were included. Extracted data were analyzed through narrative synthesis, with prevalence figures summarized where available. A total of 27 studies from various Sub-Saharan African countries met inclusion criteria, revealing a broad spectrum of occupational health challenges. Frequently reported injuries included cuts, fractures, and musculoskeletal strains, while common illnesses encompassed respiratory disorders, noise-induced hearing loss, dermatological conditions, and gastrointestinal issues. Contributing factors identified included insufficient safety training, inadequate use of personal protective equipment, environmental exposures, and weak regulatory compliance. The findings highlight the urgent need for targeted interventions, improved occupational health training, and stricter enforcement of safety policies to protect seaport workers. This review provides an evidence-based foundation to guide policymakers, port authorities, and occupational health professionals in developing effective preventive strategies.